Pedogenic components of Xijin loess from the western Chinese Loess Plateau with implications for the Quaternary climate change. (February 2019) - Guo, Benhong; Peng, Tingjiang; Feng, Zhantao; Li, Xiaomiao; Li, Meng; Ma, Zhenhua; Li, Jijun; Song, Chunhui; Zhang, Jun; Hui, Zhengchuang; Zhang, Shengda
Graphical abstract: Highlights: The <2 μm fraction of Xijin loess includes both wind-blown detrital and in situ pedogenic components. The pedogenic components are reversely correlated with the >40 μm fraction and global marine oxygen isotope. The pedogenic components are superior to the magnetic susceptibility for high-resolution reconstruction of the Quaternary climate change in the western Chinese Loess Plateau. Abstract: Chinese loess deposits preserve abundant information on the aridification of the Asian interior and Asian monsoon evolution during the Quaternary. Although substantial progress has been made in deciphering the paleoclimatic record of the thick loess deposits in the western Chinese Loess Plateau (CLP), the environmental significance of variations in the magnetic susceptibility (χ) and the ultrafine (<2 μm) grain-size is still unclear when compared with the central CLP. Here, we present high-resolution records of χ, frequency-dependent magnetic susceptibility (χfd ) and grain-size (<2 μm and >40 μm fractions) of the 416-m-long Xijin loess core from the Lanzhou Basin, northeastern Tibetan Plateau. Our results indicate that the <2 μm fraction of the core consists of both detrital dust and material produced during pedogenesis. An integrated analysis of records of χ, χfd, grain-size (<2 μm) and clay minerals reveals that the pedogenic component of the <2 μm fraction is significantly anti-correlated with the >40 μm fraction and marine oxygen isotope record. Consequently, we conclude that the pedogenic component is a more accurate and sensitive indicator of weathering and soil formation than the χ record, and it is well suited to reconstructing high-resolution Quaternary climatic change in the western CLP. Furthermore, the proportion of the pedogenic component increased systematically over the past 2.2 million years, which may have been primarily caused by long-term global cooling since the Early Pleistocene together with the episodic uplift of the Tibetan Plateau.